Contribution of Arm Muscle Explosion Power to Speed of Tennis Service - Indri Wulan Dari; Muhammad Arnando (Universitas Negeri Padang, 2019)
The purpose of this study was to reveal the contribution of arm muscle explosive power to the speed of tennis service to students of the Faculty of Sport Science, Padang State University. The population in this study were FIK UNP students who had taken basic tennis courses. While the sample is 100 students who are considered to have good servive techniques. Data obtained from the results of the arm muscle explosive power test performed with one Hand Medicine Ball, grip strength test with grip strength dynamometer while the service test was performed with Hewitt Achievement Test. Based on data analysis, it was found that the results obtained: 1) There was a contribution of arm muscle explosive power to the speed of service, where the contribution was 75.19%. Thusthe explosive power of the arm muscles contributes to the speed of service. Punch service is one of the keys to a victory. The focus of this research is to find out how much the arm muscle explosive power contributes to the speed of service. This research will be applied to 100 FIK students taking field tennis courses in 2018. The aim is to apply to students so that we can see directly how much the contribution of explosive power arm muscles towards the speed of the tennis court service, besides the contribution of other factors